2013
DOI: 10.1155/2013/370487
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Is Associated with Increased Oxidative Stress and Antioxidant Enzyme Activity in Welders

Abstract: The purpose of this study was to examine the association of vitamin B6 status and plasma homocysteine with oxidative stress and antioxidant capacities in welders. Workers were divided into either the welding exposure group (n = 57) or the nonexposure controls (n = 42) based on whether they were employed as welders. There were no significant differences in vitamin B6 status and plasma homocysteine concentration between the welding exposure group and the nonexposure controls. The welding exposure group had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…Nuernberg et al [2008] reported a significant increase in urinary 8-oxodG after 6 hrs of exposure to welding fumes, with an average concentration of 0.82 mg/m 3 , which is lower than that in our study. In contrast, Liu et al [2013] did not find any significant difference in 8-oxodG between welders and controls (though exposure levels were not reported in that study). Although 8-oxodG has a short turn-over in the body [Nuernberg et al, 2008], the urine samples for our study were collected during the last 4 hrs of an 8-hr work shift, and should thus reflect changes induced by shortterm exposures.…”
Section: Discussioncontrasting
confidence: 67%
“…Nuernberg et al [2008] reported a significant increase in urinary 8-oxodG after 6 hrs of exposure to welding fumes, with an average concentration of 0.82 mg/m 3 , which is lower than that in our study. In contrast, Liu et al [2013] did not find any significant difference in 8-oxodG between welders and controls (though exposure levels were not reported in that study). Although 8-oxodG has a short turn-over in the body [Nuernberg et al, 2008], the urine samples for our study were collected during the last 4 hrs of an 8-hr work shift, and should thus reflect changes induced by shortterm exposures.…”
Section: Discussioncontrasting
confidence: 67%
“…Our recent study has shown three-fold higher homocysteine levels in the retina from human donors with established diabetic retinopathy compared to retina from nondiabetic human donors [13]. High circulating levels of homocysteine are implicated in many cellular abnormalities, including oxidative stress, mitochondrial fission and the activation of MMP-9 [14][15][16]. The way in which elevated homocysteine regulates retinal MMP-9 activation in diabetic retinopathy is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Serum gamma-glutamyltransferase (GGT) is considered as a suitable marker for oxidative stress in epidemiological settings (Lee et al, 2004). Both homocystein (Liu et al, 2013) and uric acid (So and Thorens, 2010;Strazzullo and Puig, 2007) are considered as markers of oxidative stress and their circulating levels can be easily assessed in large scale population-based studies.…”
Section: Introductionmentioning
confidence: 99%